Up-Regulation of SALL4 Is Associated With Survival and Progression via Putative WNT Pathway in Gastric Cancer - Yang, Yang; Wang, Xiaohong; Liu, Yiqiang; Hu, Ying; Li, Zhongwu; Li, Ziyu; Bu, Zhaode; Wu, Xiaojiang; Zhang, Lianhai; Ji, Jiafu (Frontiers in Cell and Developmental Biology, 2021)
SALL4, a transcriptional factor involved in embryonic stem cell self-renewal and pluripotency, is over-expressed in gastric cancer (GC). However, the association of SALL4 with the survival of GC patients is not well understood, and the role of SALL4 in cancer progression is still unknown. In the present study, a total of 1815 GC patients who underwent radical resection at Peking Cancer Hospital were included consecutively from 2015 to 2018, confirming the prognostic value of SALL4 and validating by data from TCGA and GEO. The protein and mRNA expression levels of SALL4 were evaluated by immunohistochemistry and qPCR, respectively. Besides, GSEA and WGCNA were applied to explore the SALL4-related cancer-promoting signaling pathways and gene modules. Our results showed that overexpression of SALL4 was observed in 16.7% of GC patients. SALL4 positivity was associated with male, older age, mixed-type histology, late stages, lymphatic metastasis, vascular invasion, non-cardiac location, high AFP level and no EBV infection background. SALL4 could be served as a marker for prognostic prediction in GC, and SALL4-positive GC was significantly associated with shortened survival. Further, the bioinformatic analysis indicated that the Wnt/β-catenin signaling pathway was activated in SALL4-high cases compared with SALL4-low cases. Expression of SALL4 was also positively correlated with the expression of multiple co-expressed genes, such as, TRIB3, which plays an important role in activating the Wnt/β-catenin pathway. Our findings indicate that SALL4 is associated with clinicopathological features related to cancer progression in GC and its function in the Wnt/β-catenin pathway.